(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Innovative material known as pervious concrete has a porous structure that allows water to pass through it and provides a number of environmental benefits. The goal of the current laboratory investigation is to evaluate the properties of various pervious concrete mixtures subjected to different compaction energies. Various amounts of cement, reinforcing fibers, and aggregates with various physical, chemical, and mechanical qualities have been added to the mixtures, changing the water-to-cement ratio while keeping the aggregate size distribution and paste content constant. Pervious concrete (PC) use has a number of positive effects on the environment, the economy, and society. This study aims to assess the mechanical performance of pervious concrete by adding human hair as a reinforcing component. Fiber-reinforced concrete addresses the inherent tensile weakness of traditional concrete by increasing flexural strength and reducing crack development.